Pengaruh Gaya Hidup terhadap Kesehatan Mental Remaja - Shalahuddin, Muhammad Abdurrahman; Irsyadi, Muhammad Lingga (Maternal & Neonatal Health Journal, 2023)
This study aims to explore the relationship between modern lifestyles and adolescent mental health. The technique applied in this study is a qualitative method with a literature study approach with the aim that the information from the research results can be comprehensive. The sources used in this study include journal articles, books, and industry reports related to the influence of lifestyle on adolescents' mental health, all sources were collected with the keywords "modern lifestyle", "adolescent mental health", "technology use", "adolescent sleep patterns", "diet and mental health", and "physical activity and mental health" after which all sources were evaluated to be relevant to the research topic discussed. This study revealed the results that excessive technology use, irregular sleep patterns, unbalanced diet, and lack of physical activity contribute significantly to the increased risk of mental disorders such as anxiety and depression in adolescents. Strategies proposed to mitigate these negative impacts include encouraging healthy technology use, improving sleep quality, promoting a healthy diet, encouraging physical activity, and building strong social support.